Augmented reality in mobile devices applied to public transportation - Soto, Manuel F. (2013)
Augmented Reality (AR) is one of the most revolutionary technologies at these times. It improves the real world by additional computer generated information. The AR paradigm opens new ways for development and innovation of di erent applications, where the user perceives both, virtual and real objects at the same time. With the rise of SmartPhones and the development of its characteristics, the AR on mobile devices emerging as an attractive option in this context. In this paper we present the design, implementation and testing of an application of AR on Android platform for mobile devices. This allows a person traveling through the city gets information of routes, timeouts, etc; about a particular bus line. All this information is provided on the mobile device and associated to the real world, facilitating their interpretation.